Bimtek Manajemen Sumber Daya Manusia dan Pemasaran Pada Koperasi Produsen Pancur Agro Makmur di kelurahan Kalipancur - Askar Yunianto; J Jaeni; M Maryono; P Purwatiningtyas (LPPM STIKOM Tunas Bangsa, 2023)
The Pancur Agro Makmur Producer Cooperative in Kalipancur Village, is a newly established cooperative. This cooperative includes producer farmer group cooperatives whose members consist of various products, namely in crop cultivation, animal husbandry and fisheries, holiculture, fertilizer processing. Cooperative management is often interpreted as a way to utilize cooperative resources as economic. Farmer groups as managers between individuals and breeders, crop cultivation, fisheries, horiculture and fertilizer management. Most farmer groups have difficulty in forming capital. There are limited human resources, adeuate facilities and infrastructure owned by cooperatives and solid business networks/partnerships with the principles of interrelatedness, mutual need and mutual benefit. In term of financing and capital it still difficult for cooperatives to access financialinstitution (banking) considering the conditions set are quite severe, especially the issue of guarantees/collateral and other conditions. The effort is to increase from the capital side through productive economic endeavors. Economy is defined as series of activities to provide business capability, economy to increase, and create mutually beneficial business partnerships. Marketing is the cornerstone of the activities of a business. Including those in the prosperous Agro Producer Cooperative, Prosperous Agro Pancur producers will quikly grow and develop.